2022
DOI: 10.1007/s13668-021-00390-0
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Perceptions of Children’s Exposure to Unhealthy Food Marketing: a Narrative Review of the Literature

Abstract: Purpose of Review A key driver of unhealthy diets in children is the marketing of unhealthy foods and beverages. Attempts to regulate children’s exposure to unhealthy food marketing through government-led policies are challenged by commercial interests. Parents shoulder the responsibility of counteracting the effects of omnipresent unhealthy food marketing that children are exposed to within the food environment. In this narrative review we aimed to synthesise the evidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 71 publications
2
7
0
1
Order By: Relevance
“…Our findings support evidence showing industry-led codes are ineffective at reducing children’s exposure to unhealthy food and beverage marketing 158–161. Our results reinforce global recommendations from the WHO and other bodies to move away from a ‘child-directed’ approach to marketing restrictions, and towards actions that target all marketing that children are exposed to, or which has the intention of influencing children’s UPF consumption 157…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Our findings support evidence showing industry-led codes are ineffective at reducing children’s exposure to unhealthy food and beverage marketing 158–161. Our results reinforce global recommendations from the WHO and other bodies to move away from a ‘child-directed’ approach to marketing restrictions, and towards actions that target all marketing that children are exposed to, or which has the intention of influencing children’s UPF consumption 157…”
Section: Discussionsupporting
confidence: 83%
“…While many of TCCC’s identified marketing campaigns are not in violation of these pledges, which commonly only apply to children under the age of 12 years, they highlight how explicit TCCC is at targeting the gatekeepers of young children’s diets (mothers), and older children. These findings are concerning because of the demonstrated influence of unhealthy food and beverage marketing over children’s food and beverage preferences for and consumption of unhealthy products, with unhealthy food and beverage marketing shown to increase children’s requests for advertised products and undermine caregivers’ intentions to provide healthier foods and beverages 47 155–157. Our findings support evidence showing industry-led codes are ineffective at reducing children’s exposure to unhealthy food and beverage marketing 158–161.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…However, we must be cognizant that the demand by consumers is a key determinant of the food offered by these informal food outlets [ 58 , 66 ]. This is also the case in terms of the type of food sold in schools, as evidence [ 67 , 68 ] has shown that the reason why this food is mostly unhealthy [ 69 ] is because children demand unhealthy food [ 70 ], and their preference for this food is fueled by food marketing [ 61 ]. This has a strong policy implication; hence, policy reforms are required to increase access to affordable healthy food options in communities and schools, so as to curb the indiscriminate sale and marketing of unhealthy food.…”
Section: Diet-related Public Health Approaches Aimed For This Special...mentioning
confidence: 99%